Entre os livros do Visconde: a biblioteca da família Fernandes Pinheiro (Rio Grande do Sul – século XIX) - Rangel, Bruna Gomes (Universidade do Vale do Rio dos Sinos, 2016)
This master thesis aims to understand the elite families practices reading in Porto Alegre in the nineteenth century, from the case study of Fernandes Pinheiro Family. José Feliciano Fernandes Pinheiro, the Viscount of São Leopoldo, was a brazilian intelectual and politician, considered the first historian of Rio Grande do Sul, despite being born in Santos (RJ). The family library, listed at inventary post mortem of Viscount, was composed by 754 books. The analysis is based on theorical and methodological proposals of the New Cultural History and investigates the reading practices and meanings of accumulation and possession of libraries by segments of the nineteenth-century elites, as a lifestyle statement and self-representation. The purpose was to understand the uses of this library, not only in the immediate pleasure, but also as form of self-representation of elite individuals. In a society strongly based on notions of honor, what is the role of a collection this volume? We desnaturalized this bibliographic, considering its constitution as a familiy investment not only directed to the formation of a financial capital, but also as a simbolic capital, a insígnia of lifestyle linked to illustration and refinement.
Keywords: História da família; Práticas de leitura; Família Fernandes Pinheiro; Family history; Reading practices; Fernandes Pinheiro Family; ACCNPQ::Ciências Humanas::História